(untitled) (Journal of the College of Basic Education, 2025)
The Current Research Aims: "Know The Impact Of The Strategy Of The Four Pillars In Creative Writing When Students Of The First Intermediate Grade", And To Reach The Goal Formulated The Following Hypothesis: "There Is No Statistically Significant Difference At The Level Between The Average Scores Of The Experimental Group Students And The Average Scores Of The Control Group Students In The Post-Test Of Creative Writing", And The Research Sample Included (62) Female Students From The First Intermediate Grade In The Middle School (Nazik Al-Malaika) Of The Directorate Of Education Of Baghdad Rusafa / 2, For The Academic Year (2024-2025), The Experimental Group Included (30) Students It Studied According To The Steps Of The Strategy (The Four Pillars), While The Control Group Included (32) Students Who Studied According To The Usual Method, And The Researcher Prepared A Test For Creative Writing That Included (15) Paragraphs Of The Type Of Article Questions, And After Verifying Its Sincerity And Stability And Extracting Discriminatory Forces And Difficulty Coefficients, And Also Built A Standard For Correcting The Test And Also Verified Its Sincerity And Stability, And After The Two Groups Studied A Full Semester For The Academic Year (2024-2025) Then The Application Of The Test After Two Groups And Processing The Data Statistically, And Reached The Following: "The Students Of The Experimental Group Outperformed The Students Of The Control Group In The Post-Creative Writing Test." ", And Concluded About Its Role In Raising Their Level And The Growth Of Their Vocabulary And Eloquence, As It Recommended Its Adoption In Other Variables And Stages Of Study